Evaluation of fluorescence imaging with indocyanine green in hepatocellular carcinoma. Issue 1 (December 2016) - Kaibori, Masaki; Matsui, Kosuke; Ishizaki, Morihiko; Iida, Hiroya; Sakaguchi, Tatsuma; Tsuda, Takumi; Okumura, Tadayoshi; Inoue, Kentaro; Shimada, Shingo; Ohtsubo, Seiji; Kusano, Mitsuo; Ikehara, Yuzuru; et al.
Abstract Background We hypothesized that indocyanine green (ICG) fluorescence patterns using Clairvivo OPT in resected liver specimens could confirm hepatocellular carcinoma (HCC) better than earlier commercial imaging systems. This preclinical trial evaluated the effectiveness of fluorescence imaging as an intraoperative cancer navigation tool. Methods ICG fluorescence images of resected specimens from 190 patients with HCC were classified into two groups according to whether high fluorescence was seen in the HCC (high cancerous [HC] group) or in the surrounding liver tissue (high surrounding [HS] group). The HC and HS groups were sub-classified into whole and partial types and whole and ring types, respectively. Results The HC group had significantly higher prevalence of esophageal or gastric varices, and worse liver function than patients in the HS group. The HC group also had a higher percentage of limited resection cases than did the HS group. Cirrhotic liver histology was significantly more common in the HC group than in the HS group. Multivariate analysis revealed that the HC group was a predictive factor for cirrhosis in HCC patients. Among the HC patients, a higher percentage of well-differentiated HCC cases were seen in the partial-type subgroup than in the whole-type subgroup (23/48 (48 %) vs. 7/68 (10 %)). In the HS group, the ring-type subgroup had a higher percentage of poorly differentiated HCC cases than did the whole-type subgroup (6/37 (16 %) vs. 0/37 (0 %)). Conclusion Tumor differentiation and fibrosis in the non-cancerous liver parenchyma could affect ICG fluorescence imaging in HCC. ICG fluorescence imaging may be a good indication for fibrosis stage. In future, we will try to evaluate fluorescence imaging with ICG for intraoperative cancer navigation in HCC, using a portable near-infrared fluorescence imaging system.